TEKNIK PERMAINAN DAN PENYAJIAN NEVICATA OPUS 29 PASTORALE KARYA BENVENUTO TERZI - Berutu, Kristin Advent J; Kartini R.M Manalu (Universitas Hamzanwadi, 2024)
This study discusses the interpretation and presentation techniques of Nevicata Op. 29 Pastorale by Benvenuto Terzi. The techniques used are interpretation techniques based on musical elements such as dynamics, tempo, and playing techniques in the form of barre, vibrato, arpeggio, harmonics, trills, glissando, slur, nano izi quardo solo, tone color, apoyando, tirando, sul tasto, and sul ponticello techniques. This study also explains the difficulties experienced by the author when presenting nevicata in a recital and how to overcome them during the practice process. The very basic level of complexity in this nevicata is the use of larghissimo (slow) and piano (soft) tempos. In the last section, the author explains the presentation of nevicata op. 29 when performing a recital.